2020
DOI: 10.1109/access.2020.3025782
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Optimal Deployment of Several DGs in Distribution Networks Using Plant Propagation Algorithm

Abstract: In recent years, the substantial upsurge of electricity demand has directly impacted the performance of the distribution networks concerning the active power losses and voltage drops. In such circumstances, the distributed generators (DGs) could uphold these concerns if they are optimally deployed in terms of sizing and placement. For this reason, in current research, the optimal deployment of DGs has been proposed with the plant propagation algorithm (PPA) to simultaneously maximize the total active power los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…The authors in [14] suggested the plant propagation algorithm (PPA) to maximize active loss reduction and minimum bus voltage by integrating 1-4 DGs in Type-I into IEEE 33 and 69-bus RDNs.…”
Section: B Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors in [14] suggested the plant propagation algorithm (PPA) to maximize active loss reduction and minimum bus voltage by integrating 1-4 DGs in Type-I into IEEE 33 and 69-bus RDNs.…”
Section: B Literature Reviewmentioning
confidence: 99%
“…Also, comparison of the convergence and maximum iteration numbers with those in literature is listed in Table 9. No DG GA [8] EGOA [33] DAPSO [2] ALOA [59[ ALOA [36] PPA [14] GA PSO GA [8] EGOA [33] PSO GA DAPSO [2] ALOA [36] PPA [14] PPSO [1] 1DG 2DG…”
Section: B Case Study 1: For Peak Loadmentioning
confidence: 99%
“…In this section, ORPD is solved using FPSOGSA with RERs. With the uncertainties of the load, solar irradiance and the wind speed, voltage deviations and the expected stability index according to (17), (18) and (19). Table XI shows the percentage load demands for each scenario and the output powers from the 25 scenarios can be obtained.…”
Section: B Orpd Problem With Uncertainty Of Rersmentioning
confidence: 99%
“…However, they have some of difficulties to solve the intricated problem of ORPD such as trapping into the local minima, premature convergence and the algorithmic complexity. To resolve these problems, the development of the new meta-heuristic optimization techniques like differential evolution technique, whale optimization algorithm, sine cosine algorithm, moth-flame optimization, ant lion optimizer algorithm, cuckoo search algorithm, plant propagation algorithm, grey wolf algorithm and particle swarm optimization [14][15][16][17][18][19][20][21] are developed to overcomes these issues. The new hybrid techniques are used for the conventional thermal units to solve ORPD.…”
Section: Introductionmentioning
confidence: 99%
“…The objective function formulated for the studied optimization methodology aims towards active and reactive power losses reduction, improvement in bus voltage profile and high reliability index of the system. The plant propagation algorithm is used in [16] for the optimal deployment of the DGs by simultaneously maximizing the total active power loss reduction and upgrading the magnitude of bus voltages. In [17], a two-stage gametheoretic approach is employed for residential PV panels placement planning integrated with the energy shaving mechanism to increase financial benefits.…”
Section: Introductionmentioning
confidence: 99%